Truth and reconciliation in South Africa: did the TRC deliver? - Chapman, Audrey R.; Van der Merwe, Hugo (Pennsylvania studies in human rights, 2008)
Preface / Audrey R. Chapman and Hugo van der Merwe -- Introduction : assessing the South African transitional justice model / Audrey R. Chapman and Hugo van der Merwe -- What survivors say about justice : an analysis of the TRC victim hearings / Hugo van der Merwe -- The TRC's approach to promoting reconciliation in the human rights violations hearings / Audrey R. Chapman -- Perspectives on the role of forgiveness in the human rights violations hearings / Audrey R. Chapman -- An evaluation of the South African amnesty process / Jeremy Sarkin -- The impact of the TRC's amnesty process on survivors of human rights violations / Timothy Sizwe Phakathi and Hugo van der Merwe -- Levels of truth : macro-truth and the TRC / Audrey R. Chapman and Patrick Ball -- Truth recovery through the TRC's institutional hearings process / Audrey R. Chapman -- Object of trust and hatred : public attitudes toward the TRC / Gunnar Theissen -- Reaping what you sow : political parties, the TRC, and the quest for truth and reconciliation / Piers Pigou -- Did the TRC deliver? / Hugo van der Merwe and Audrey R. Chapman -- Reflections on the South African experience / Audrey R. Chapman and Hugo van der Merwe